Bamboo innovator village a countryside landscape development strategy through the thriving bamboos applied at Barangay Lambac, Talim Island, Cardona Rizal - Gervacio, Margaret Emmanuell DC
Rural areas were often forgotten with the fast paced developments in urban. On a regular basis, people who are living in these areas become passive and dependent on their resources processed in urban settlements. Utilization of raw materials which are initially found near rural areas are not maximized properly which leads to economic and ecological problems. This study explores the application of countryside landscape development strategy as being applied in Barangay Lambac's Bamboo culture. The study focuses on the community development of Barangay Lambac and serves as a framework to produce a synthesized and apt spatial plan and design. With the intervention of Landscape Architecture methods, the community development applied in Barangay Lambac can be deemed effective to cater the needs of the people.